Cognitive-motor interventions based on virtual reality and instrumental activities of daily living (iADL): an overview - Buele, Jorge; Palacios-Navarro, Guillermo (Frontiers in Aging Neuroscience, 2023)
Non-invasive and non-pharmacological interventions using virtual reality (VR) are a tool that seek to 12 improve cognition in patients with degenerative cognitive disorders. Traditional therapies called 13 "pencil and paper" are not aimed at practicing daily activities that the elderly experience in their 14 environment. These activities represent a challenge for the person, both in the cognitive and motor 15 aspects, so it is necessary to know the results of this type of combined interventions. The aim of this 16 review was to analyze the benefits of cognitive-motor VR applications that simulate instrumental 17 activities of daily living (iADL). Five databases were systematically searched: Scopus, Web of Science, 18 Springer link, IEEE Xplore, and Pubmed from inception to January 31, 2023. The main findings of this 19 review include activation of certain areas of the brain by motor movement together with improvements 20 in general cognition, executive function, attention and memory. Cognitive-motor interventions based 21 on VR and iADLs can be beneficial for the elderly, since better cognitive and motor performance 22 translate into increased autonomy in activities and a better quality of life.